Improving Students’ Ability in Understanding Reading Texts Using the SQ4R Method - Sitti Aminah; Nurmalawati (Proceeding of International Conference on Multidisciplinary Research, 2024)
The aim of this research is to determine the effect of using the SQ4R method in improving students' ability to understand reading texts. The stages of this research method include initial observation, pretest, learning process, posttest and discussion of the results of reading learning using the SQ4R method. This research uses a quantitative method in the form of a quasi-experiment in the form of testing a learning method with the object of research being class XI students at SMAN I Lhokseumawe. This research instrument is in the form of test questions and interview guidelines. This research will later become a benchmark for further learning for class XI students in the current year, especially in Indonesian language lessons, but can also be used in other learning. Based on the results of research conducted at SMAN 1 Lhokseumawe, there was an increase in standard grades in the experimental class. Meanwhile, in the control class there was no change in the learning process in terms of grades. This can be seen from the test results of the difference in average post-test scores t= 0.092 < 2.021, sig.= 0.001 > 0.05 from a total of 22 students. Based on the results of this research, it can be concluded that there has been an increase in the ability to understand reading texts in students whose learning uses the SQ4R method.